Interpretative Structural Modeling Dalam Analisis Kelembagaan Pengendalian Kualitas Air Waduk Sutami - Nisa', Syadzadhiya Qothrunada Zakiyayasin; Sitogasa, P. S. Ardisty; Fadila, Kabul; Munir, Syahrul (Jurnal EnviScience (Environment Science), 2022)
The Sutami Reservoir, located in Malang Regency, East Java, has moderate to severe levels of pollution. This pollution problem can reduce the water quality of the Sutami Reservoir, so it requires coordination from the agencies concerned to formulate water pollution control policies. The management agency for the Sutami Reservoir is the ‘Perum Jasa Tirta 1’ (PJT 1). The institutional analysis applied is the Interpretative Structural Modeling (ISM) method, to find out which agencies are key elements/factors. There are eleven agencies analyzed. Agencies that are included in the ‘Dependent’ sector are the Water Resources Public Works Office, the Tourism and Culture Office, the Livestock and Animal Health Office, the Population Control and Family Planning Office, and the rice farmer groups. Institutions in the ‘Linkage’ sector are the Food Crops, Horticulture, and Plantations Office and the Industry and Trade Office. Institutions in the ‘Independent’ sector that play a key role are the Environment Office, the Fisheries Office, Balai Besar Wilayah Sungai Brantas, and the floating net cage fish farmer group. These four agencies are the key elements that have a big driving power so that more in-depth coordination needs to be carried out for the formulation of policies and regulations for water quality control.